Analisis Komparatif Pola Kerjasama dan Koordinasi Petani Padi di Ciracap dan Rancaekek - Rasmikayati, Elly; Suminartika, Eti; Saefudin, Bobby Rachmat (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
There are many factors that influence the sustainability of rice farming, including social factors, namely cooperation and coordination between farmers. However, the level of farmer participation in cooperation and coordination can differ from one region to another. The purpose of this study was to describe the factors that influence cooperation and coordination of rice farmers and then compare them between rice farmers in Ciracap District, Sukabumi Regency and Rancaekek District, Bandung Regency. The design of this study used quantitative research with a comparative approach. The population in this study were rice farmers in Ciracap and Rancaekek Districts with a sample size of 44 rice farmers in Ciracap District and 41 rice farmers in Rancaekek. The results of the study showed that there were significant differences in terms of cooperation and coordination between rice farmers in Ciracap and Rancaekek. Rice farmers in Ciracap were stronger in carrying out cooperation and coordination between their farmers than rice farmers in Rancaekek.